First report of in vitro resistance of Psoroptes ovis to ivermectin in Argentina - Soler, Paula; Germano, Monica Daniela; Larroza, Marcela Patricia (Elsevier, 2022)
Sheep scab, or psoroptic mange, a disease caused by the mite Psoroptes ovis, is commonly treated with ivermectin (IVM) and other macrocyclic lactones. In Argentina, in vivo trials have shown a decrease in IVM effectiveness to treat both sheep and bovine scab. In this work, we used an in vitro technique to establish the efficacy of IVM and two other macrocyclic lactones, doramectin (DRM) and moxidectin (MXD), against P. ovis in sheep. Mites were exposed to plates with culture medium and either ethanol or each of the acaricides, and mite mortality at a diagnostic concentration of IVM was assessed. Total survival in one of the strains studied demonstrated the presence of resistance, associated with control failures previously described by the authors. These resistant mites also presented larger LC50 values for both DRM and MXD than expected. Since, in in vivo trials, we had also previously observed a decrease in DRM effectiveness, cross-resistance may exist between DRM and IVM. We propose the use of in vitro tests to evaluate the efficacy of acaricides, considering their practicality, low cost and proven usefulness in detecting resistance in cases of low effectiveness against sheep scab